Brachythecium funkii Schimp. and B. japygum (Głow.) Köckinger & Jan Kučera comb. nov., two Alpine species hitherto included in B. cirrosum (Schwägr.) Schimp. (1st October 2016) - Köckinger, Heribert; Kučera, Jan
Abstract : Morphological and molecular studies support the recognition of three alpine species within the traditional concept of Brachythecium cirrosum, which requires the resurrection of two earlier described taxa, B. funkii and B. japygum, comb. nov., from synonymy. According to nuclear and chloroplast sequence data, the latter two taxa proved to be closely related to B. tommasinii and B. tenuicaule, whereas the affinities of B. cirrosum within Brachythecium are rather unclear. B. funkii is a coarser plant than B. cirrosum and also differs in shorter leaf acumens and much larger lamina cells. On the other hand, B. japygum (better known under the illegitimate name Eurhynchium histrio ) can be distinguished from B. cirrosum in the prostrate and densely pinnate to subdendroid growth form, longer leaf acumens and wider lamina cells with lumens wider than walls. All three species also differ from each other in the morphology of the alar cell group. Despite their shared preference for calcareous rocks, the three species show marked differences in habitat requirements.